METODOLOGI IJTIHAD DALAM EMPAT MAZHAB DAN RELEVENSINYA TERHADAP HUKUM ISLAM KONTEMPORER - Winda Innayah, Lailatul; Rahmawati, Titin; Khairunnisa, Alfira; Farah Nazila, Shabrina; Siyono (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
Ijtihad is the main epistemological instrument in the development of Islamic law and functions as a mechanism for responding to new legal issues that are not explicitly regulated in primary textual sources. Historically, ijtihad has produced diverse legal methodologies through the four major Sunni schools of law: Hanafi, Maliki, Syafi‘i, and Hanbali, each of which developed distinctive approaches to legal derivation (istinbāṭ) influenced by their respective social and intellectual contexts. Previous studies emphasize the importance of collective ijtihad and the integration of maqasid syari‘ah in contemporary legal reasoning. This study aims to describe the methodologies of ijtihad within the four mazhab, analyze their similarities and differences, and examine their relevance in addressing contemporary Islamic legal issues. This research employs a qualitative approach based on library research, utilizing classical Islamic legal literature and contemporary academic journals.